Assessing the quality of child investigative interviewing in the Netherlands. Issue 5 (29th January 2019) - Otgaar, Henry; La Rooy, David; Horselenberg, Robert; Hershkowitz, Irit; de Ruiter, Corine; Blezer, Laura; Kidane, Rosie; Kollau, Rowan
Summary: Using evidence‐based guidelines to interview children is an important means to obtain complete and accurate accounts. In the current study, we examined the quality of child investigative interviewing in the Netherlands. To examine this, we compared the Dutch Scenario Model with the National Institute of Child Health and Human Development Protocol and interviews from countries that did not follow a specific protocol. Our principal result was that Dutch child interviewers rarely asked recommended open prompts that are known to elicit detailed and accurate testimonies from children. Furthermore, we found that the scenario model contained the highest number of directive questions compared with interviews from other countries. Our findings show that the Dutch Scenario Model is not well aligned with current research‐based recommendations for interviewing children.